Tracing the Progression of Motivated Learning Strategies: an In-Depth Bibliometric Analysis - Mubarok, Fahmi Ulum Al; Azani, Mohammad Zakki; Salim, Hakimuddin; Maksum, Muh. Nur Rochim; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to map and analyze the development of studies on Education Strategies in publications indexed in Scopus. Methods: The approach used is bibliometric analysis, exploring publications on 'Motivated Strategies of Learning' in the Scopus database from 1977 to 2023. The analysis process involved the use of tools such as Excel and R/R-Studio. Visual analysis was conducted using VOSviewer to visualize keyword occurrences and document citations simultaneously. Result: In this study, 942 relevant publications meeting the specified criteria were identified. Findings indicate an annual growth rate of 9.5%, peaking in 2020. The United States emerged as the primary contributor in publications, with Middle East Technical University Turkey being the most productive affiliation. The most prolific author in the Motivated Strategies of Learning theme was Sungur, S. Value: This research provides a comprehensive overview of the literature in the field of education, with recommendations for future research directions. This study will likely make a valuable contribution to understanding educational strategies.